2015
DOI: 10.1360/n052014-00314
|View full text |Cite
|
Sign up to set email alerts
|

Ecologically Based Pest Management at Multiple Spatial Scales

Abstract: Patch composition structure and landscape pattern at different spatial scales have great variation. Scale effect is also an important characteristics in agricultural landscape. In recent years, both agricultural management within field and landscape modification at landscale scale were used to achieve ecologically based pest management and ecosystem services. Ecologically based pest management should be conducted at multiple spatial scales, especially the combination of farming activities at local scale and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
4
0
2
Order By: Relevance
“…We hypothesize that this result is affected by both the composition of the crop and predators in the landscape. The resource concentration hypothesis suggests that phytophagous insects prefer to live in a single host plant habitat (Zhao Z. H. et al, 2015). In this study, the other crops planted around the tomato field in the water landscape were mainly Nelumbo nucifera Gaertn (Proteales: Nelumbonaceae), Vitis vinifera L. (Rhamnales: Vitaceae), and Allium tuberosum L. (Liliflorae: Liliaceae).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We hypothesize that this result is affected by both the composition of the crop and predators in the landscape. The resource concentration hypothesis suggests that phytophagous insects prefer to live in a single host plant habitat (Zhao Z. H. et al, 2015). In this study, the other crops planted around the tomato field in the water landscape were mainly Nelumbo nucifera Gaertn (Proteales: Nelumbonaceae), Vitis vinifera L. (Rhamnales: Vitaceae), and Allium tuberosum L. (Liliflorae: Liliaceae).…”
Section: Discussionmentioning
confidence: 68%
“…Studies have shown that landscape factors are the key drivers of predator abundance (Woltz et al, 2012). The natural enemy hypothesis suggests that diverse plant communities can increase natural enemy populations (Zhao Z. H. et al, 2015). Flowering plants can significantly increase the life span of natural enemies and the number of their eggs (Lisa and Steve, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Biological control ecological agricultural engineering adopts biological methods to carry out comprehensive treatment and reduce or even completely avoid the use of chemical pesticides [12]. Pest ecological regulation is an ecological strategy, such as promoting crop health and soil health on the field scale, setting up the spatial shelter, transfer habitat and overwintering environment for pest natural enemies on the landscape scale, restoring the resistance of the ecosystem to the greatest extent [13], planting plants conducive to natural enemies of pests to build an environmental system with strong natural biological control ability, and releasing natural enemies of pests during their spawning period to reduce the population base of pests.…”
Section: ) Ecological Agricultural Engineering Of Pest Regulationmentioning
confidence: 99%
“…另外, IPM最大的特点是依靠外界物质和能量的 投入, 来维持农业生态系统的高产出和稳定性. 虽然 IPM体系为农业生产力水平提高做出了卓越的贡献, 但形成了人类物质能量投入与害虫种群危害之间博 弈对抗的局面, 双方不断改进博弈方式和强度, 形成 了一种协同进化过程 [23,24] , 此过程中, 虽然害虫种群 危害强度和频率不断增加, 人类物质和能量的投入 也不断增加, 最终给整个农业生态系统造成了极大 的负担 [25] . 在这种对抗加剧的背景下, "虫害攻坚战", [26,27]…”
Section: 虽然Ipm已经得到了全面的应用 但在目前全球unclassified
“…间套作及轮作等, 但整个EBPM系统仍然需要大量的 技术补充和理论完善, 至少5方面还需要进一步的研 究 [59,60] : (ⅰ) 尺度效应: 昆虫在不同的时空尺度下对 环境变化的响应具有不对称性, 并且昆虫的分布及 种群动态与时空尺度密切相关, 因此需要探索害虫 种群动态及群落组成在不同时空尺度下的格局转换 和演化过程, 尤其是害虫及天敌种群的时空扩散及 流动规律随时空尺度的变化规律 [25,47] . (ⅱ) 群落食 物网拓扑学及功能群: 害虫-天敌的食物网拓扑学结 构及功能解析能够揭示害虫暴发成灾机制, 也能够 阐明每个物种在生态系统中的功能和地位, 并进一 步探索群落功能群特征和多样性模式 [61,62] .…”
Section: 虽然我国害虫生态调控技术在很多方面取得了 巨大进展 如作物多样性种植、转基因棉、减免耕、unclassified